Selected Abstracts Presented at MHM 2023 - Participants of MHM2023 (The Journal of Medicine, Humanity and Media, 2023)
For Medicine, Humanity, and Media International Conference this year, a total of 82 papers were submitted. 27 oral presentations and 22 poster presentations received acceptance after the peer-review procedure. A conference proceeding is now in preparation for publication, consisting of 13 English abstracts and 18 Chinese abstracts authorized by their respective authors. This proceeding covers a broad spectrum of topics in health communication, such as health information behaviors, misinformation, doctor-patient communication, and global health communication, and encompasses both qualitative and quantitative methodologies. Notably, align with the overarching theme “Health Communication in the Process of Digitalization", several graduate student authors employed big data, machine learning, and information tests. We extend a cordial invitation for insightful comments and scholarly citations regarding this proceeding, so as to support and foster the academic growth of graduate students.